Immigration and Voting Patterns in the European Union: Evidence from Five Case Studies and Cross-Country Analysis - Ethan Grumstrup; Todd A. Sorensen; Jan Misiuna; Marta Pachocka (Institute of Labor Economics (IZA), 2021)
Tempers flared in Europe in response to the 2015 European Refugee Crisis prompting some countries to totally close their borders to asylum seekers. This was seen to have fueled anti-immigrant sentiment, which grew in Europe along with the support for far-right political parties that had previously languished. This sparked a flurry of research into the relationship between immigration and far-right voting, which has found mixed and nuanced evidence of immigration increasing far-right support in some cases, while decreasing support in others. Studies by Mendez and Cutillas (2014); Mayda, Peri, and Steingress (2016); Vertier and Viskanic (2018); and Georgiadou, Lamprini, and Costas (2018) found that the presence of immigrants decreased votes for right parties, while others by Otto and Steinhardt (2014); Dustmann, Vasiljeva, and Damm (2016); Halla, Wagner, and Zweimuller (2017); Brunner and Kuhn (2018); and Edo et. al. (2019) found that immigration increased votes for right parties. To provide more evidence to this unsettled debate in the empirical literature, we use data from over 400 European parties to systematically select cases of individual countries. We augment this with a cross-country quantitative study. Our analysis finds little evidence that immigrant populations are related to changes in voting for the right. Our finding gives evidence that factors other than immigration are the true cause of rises in right voting.
Keywords: J15; F22; D27; 330; European Union; immigration; voting